Attachment Patterns in Children and Adolescents With Gender Dysphoria - Kozlowska, Kasia; Chudleigh, Catherine; McClure, Georgia; Maguire, Ann M.; Ambler, Geoffrey R. (Frontiers in Psychology, 2021)
The current study examines patterns of attachment/self-protective strategies and rates of unresolved loss/trauma in children and adolescents presenting to a multidisciplinary gender service. Fifty-seven children and adolescents (8.42–15.92 years; 24 birth-assigned males and 33 birth-assigned females) presenting with gender dysphoria participated in structured attachment interviews coded using dynamic-maturational model (DMM) discourse analysis. The children with gender dysphoria were compared to age- and sex-matched children from the community (non-clinical group) and a group of school-age children with mixed psychiatric disorders (mixed psychiatric group). Information about adverse childhood experiences (ACEs), mental health diagnoses, and global level of functioning was also collected. In contrast to children in the non-clinical group, who were classified primarily into the normative attachment patterns (A1-2, B1-5, and C1-2) and who had low rates of unresolved loss/trauma, children with gender dysphoria were mostly classified into the high-risk attachment patterns (A3-4, A5-6, C3-4, C5-6, and A/C) (χ2=52.66; p<.001) and had a high rate of unresolved loss/trauma (χ2=18.64; p<.001). Comorbid psychiatric diagnoses (n=50; 87.7%) and a history of self-harm, suicidal ideation, or symptoms of distress were also common. Global level of functioning was impaired (range 25-95/100; mean=54.88; SD=15.40; median=55.00). There were no differences between children with gender dysphoria and children with mixed psychiatric disorders on attachment patterns (χ2=2.43; p=.30) and rates of unresolved loss and trauma (χ2=0.70; p=.40). Post hoc analyses showed that lower SES, family constellation (a non-traditional family unit), ACEs—including maltreatment (physical abuse, sexual abuse, emotional abuse, neglect, and exposure to domestic violence)—increased the likelihood of the child being classified into a high risk attachment pattern. Akin to children with other forms of psychological distress, children with gender dysphoria present in the context of multiple interacting risk factors that include at-risk attachment, unresolved loss/trauma, family conflict and loss of family cohesion, and exposure to multiple ACEs.